Java Programming Language Learning Application Based on Octalysis Gamification Framework - Leon Christopher; Alexander Waworuntu (IJNMT (International Journal of New Media Technology), 2021)
Java programming language is rated as the second most active language in the world based on GitHub active repository statistic. Meanwhile, many university students are found lack interest to learn Java. Many researches have shown the positive impact of gamification in many areas of life, include education and learning. The purpose of this study is to design and build an application to learn java programming language with gamification in mind. We use Octalysis Gamification Framework to design the usage of game mechanics in the application. The application was tested on second year students to learn Java for the first half semester and evaluated using the Unified Theory of Acceptance and Use of Technology (UTAUT) Model and get the result of 74.27% agree that the application is well accepted by the students. Index Terms—gamification; java programming language; octalysis gamification framework